Men who suffered intimate partner violence: Impressions about existing public campaigns and recommendations for new ones - Reis, E. (2022)
Over the last decades, the negative effects of intimate partner violence (IPV) directed at men in abusive different-sex and same-sex relationships have been increasingly investigated. Men who are the targets of IPV face many barriers to help-seeking, and to overcome them, public awareness campaigns have been developed. Women who experienced IPV have found campaigns targeting them to be harmful and misleading, and previous research suggests that following the principles of formative evaluation research may improve campaigns’ effectiveness and reduce unwanted negative effects. This article documents the theory-based formative evaluation research conducted with 14 men abused in different-sex and same-sex relationships for the creation of targeted campaigns. Through semi-structured interviews, men were asked about their overall knowledge of campaigns, their thoughts about specific pictorial IPV campaigns, and their suggestions for the development of new campaigns. Thematic analysis and a theoretically grounded coding scheme were used to analyze the content of the interviews with high inter-rater reliability. Overall, our results indicate that most men were not aware of campaigns in Portugal, and their impressions about the ones they recalled were mixed. Most men praised clear messages informing forms of violence, while some responded negatively to the inclusion of words such as “shame” and “victim”, and the depiction of bruises. They also considered that future campaigns targeting men should portray “real people” like them and provide information on self-efficacy, the efficacy of recommended responses, and threat susceptibility. Our findings are consistent with previous evidence with women who experienced IPV but also provide theoretically grounded novel contributions and highlight the importance of considering the population of interest’s insights when developing and testing new campaigns.